Proyek Pemasaran Digital untuk Meningkatkan Brand Awareness dan Brand Loyalty Melalui Optimasi Social Media dan Email Marketing pada Titik Awal Kopitiam Jatinangor di Kabupaten Sumedang - Agnees Velicia Pardede; Muhammad Ramadhani; Camelia Rizki Agrina (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Titik Awal Kopitiam Jatinangor is an MSME in the culinary sector that has not yet fully optimized its digital marketing strategy. The main issues faced include low brand awareness and brand loyalty due to an unstructured and impersonal approach to social media and membership programs. This project aims to improve brand awareness and brand loyalty through the optimization of social media (Instagram and TikTok) and the implementation of email marketing based on Customer Relationship Management (CRM). The methods used include rebranding, developing a content marketing strategy through content pillars and a content calendar, and customer segmentation for more relevant email campaigns. The project showed significant performance improvements: Instagram followers increased by 4.33%, reach grew by 223%, and impressions rose by 84%. TikTok recorded a 70.76% increase in followers, 7,615% in reach, 4,470% in views, and 119.44% in likes. Email marketing achieved an open rate of 36.8% and a delivery rate of 97.7%. The membership repeat purchase rate also increased from 17.18% to 22.39%. These results demonstrate that the integration of social media and CRM-based email marketing is effective in enhancing brand awareness and brand loyalty. This project also contributes theoretically to the development of digital marketing strategies for MSMEs, particularly in the coffee shop sector.